ON THE OPTIMAL CONTROL COMPUTATION OF LINEAR SYSTEMS - Tjahjana, H.; Pranoto, I.; Muhammad, H.; Naiborhu, J. (IndoMS, 2009)
In this paper, we consider a numerical method for designing optimal controlon Linear Quadratic Regulator (LQR) problem. In the optimal control design process through Pontryagin Maximum Principle (PMP), we obtain a system of diferential equations in state and costate variables. This system lacks of initial condition on the adjoint variables, and this situation creates classic dificulty for solving optimal control problems.This paper proposes a constructive method to approximate the initial condition of the adjoint system.DOI :Â http://dx.doi.org/10.22342/jims.15.1.40.13-20